2013
DOI: 10.1097/mcg.0b013e318293a825
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a Prognostic Index of Nutritional Status in Concurrent Cirrhosis and Hepatocellular Carcinoma

Abstract: Sarcopenia is present in almost one third of patients with HCC, and constitutes a strong and independent risk factor for mortality. Our results highlight the importance of body composition assessment in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
191
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(204 citation statements)
references
References 13 publications
8
191
1
4
Order By: Relevance
“…Sarcopenia and myosteatosis have been significantly associated with a range of adverse outcomes including increased rate of post‐operative complications,10, 11, 40, 41, 42 longer length of hospital stay,41, 43 30‐day post‐operative mortality and in‐hospital mortality,44 and dose‐limiting toxicities 5, 6, 7, 8, 45, 46, 47, 48, 49, 50. In addition, the conditions have been demonstrated as independent predictors of reduced overall survival 18, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64. The situation is further complicated by the obesity epidemic that has been progressively worsening in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia and myosteatosis have been significantly associated with a range of adverse outcomes including increased rate of post‐operative complications,10, 11, 40, 41, 42 longer length of hospital stay,41, 43 30‐day post‐operative mortality and in‐hospital mortality,44 and dose‐limiting toxicities 5, 6, 7, 8, 45, 46, 47, 48, 49, 50. In addition, the conditions have been demonstrated as independent predictors of reduced overall survival 18, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64. The situation is further complicated by the obesity epidemic that has been progressively worsening in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of muscle measurement and sarcopenia definitions that were used are summarized in Table 2. Nine studies reported the cross-sectional muscle area with corresponding skeletal muscle index (12)(13)(14)17,(22)(23)(24)(25)30), whereas the psoas area was reported in eight studies (15,16,18,19,21,(26)(27)(28) and the dorsal muscle group area was reported in one study (20). One study calculated the morphometric age (calculated with total psoas area, psoas density, and abdominal aortic calcifications) (29).…”
Section: Resultsmentioning
confidence: 99%
“…From these 28 records, eight studies assessed muscle mass with means other than CT and one study was performed in a population other than patients awaiting or undergoing liver transplantation. The remaining 19 studies, including 3803 patients in partly overlapping cohorts, were included in this systematic review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Cross-referencing yielded no additional records.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various imaging modalities, such as dual‐energy X‐ray absorptiometry, computed tomography (CT), magnetic resonance imaging, and bioimpedance analysis, CT seems the best suited to measuring skeletal muscle mass in clinical settings, particularly in the surgical field, as CT is usually performed as part of the pre‐operative work‐up and during follow‐up. Although several studies from Western countries have proposed different cut‐offs for low skeletal muscle mass as calculated from CT,2, 3, 5 such values would differ from those in Asian populations, due to general differences in characteristics such as body size, lifestyles, and other factors. We have previously established new diagnostic criteria for low skeletal muscle mass by using the psoas muscle mass index from healthy young Asian adults, which was adopted in the Japan Society of Hepatology guidelines for sarcopenia in liver disease 13, 14.…”
Section: Introductionmentioning
confidence: 99%